Chronic consumption of calabash chalk diet impairs locomotor activities and social behaviour in Swiss white Cd-1 mice - Bright Owhorji; Udemeobong Okon; Azubuike Nwankwo; Eme Osim (Heliyon, 2019)
There are safety concerns as regards the consumption of Calabash chalk which is common practice in some localities in Africa and Asia. Calabash chalk contains lead (Pb) and arsenic which are believed to be harmful to the brain and responsible for cognitive dysfunction. It is possible that calabash chalk consumption may affect other neuronal activities in the body such as locomotion and social behaviour. Hence, this present research study investigated the effects of consumption of this diet on locomotion and social behaviour in mice. Forty-five Swiss white mice of mixed sex were randomly assigned into 3 groups of 15 mice each. Group 1 served as control, while groups 2 and 3 received low and high doses of calabash chalk diets respectively. Feeding lasted for 30 days and thereafter their locomotor and social behaviors were assessed. Their locomotor behaviour was assessed using the open field maze while their social behaviour was studied with the aid of nesting behaviour test. Results showed that the calabash chalk diet-fed mice had significantly reduced (p < 0.05) line crossing frequency compared to control. The nesting score of the calabash chalk diet-fed mice was significantly lower (p < 0.05) compared to control. In conclusion, consumption of calabash chalk impairs locomotion and social behaviour in mice.